Optimization of nitrogenase activity in chickpea nodules on typical chernozem steppe of Ukraine - Новицька, Н. В.; Барзо, І. Т. (Scientific Progress & Innovations, 2013)
The results of the effect of fertilizers and seed inoculation on the efficiency and productivity of nitrogenasation of chickpea varieties Roseanne are reported. The application of nitrogen fertilizer on the Right Bank of typical chernozem steppe of Ukraine promotes interaction of mineral nitrogen from natural populations of nodule bacteria. Yield of chickpea varieties Roseanne on variants without the application of fertilizer and inoculation was higher than in the variants with fertilizers normally N30P60K60 without inoculation of seeds.